1976
DOI: 10.1021/j100547a005
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox chemistry of iron(III) chloride and iron(III) perchlorate in aqueous media. A comparative study

Abstract: Photoredox chemistry of iron(III) chloride and iron(III) perchlorate in aqueous media was investigated in the wavelength range 250-425 nm. The effects of incident intensity, iron(III) and iron(II) concentrations, wavelength of irradiation, chloride concentration, radical scavengers, pH, time of irradiation, and temperature on product quantum yields were investigated. The primary photoreaction is postulated to be Fe3+-OH--Fe2+ 4--OH in iron (III) chloride and iron(III) perchlorate solutions; secondary reactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 3 publications
5
35
0
Order By: Relevance
“…7.2) creates a short-lived OH · radical which is destroyed by reaction with other redox-sensitive species (Collienne 1983;Kimball et al 1992;Voelker et al 1997), such as dissolved organic carbon (DOC). David and David (1976) showed that photo-reduction of Fe(III) occurs in the ultraviolet (UV) to near-UV region of 200 to 450 nm, with a local maximum near 300 nm, and is sensitive to changes in pH, temperature, light intensity, major solute chemistry, and Fe(II) concentration. Collienne (1983) found that maximum Fe(III) photo-reduction rates take place in the pH range 2 to 4 where Fe(OH) 2+ is the dominant dissolved ferric species.…”
Section: Modelling Schwertmannite Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…7.2) creates a short-lived OH · radical which is destroyed by reaction with other redox-sensitive species (Collienne 1983;Kimball et al 1992;Voelker et al 1997), such as dissolved organic carbon (DOC). David and David (1976) showed that photo-reduction of Fe(III) occurs in the ultraviolet (UV) to near-UV region of 200 to 450 nm, with a local maximum near 300 nm, and is sensitive to changes in pH, temperature, light intensity, major solute chemistry, and Fe(II) concentration. Collienne (1983) found that maximum Fe(III) photo-reduction rates take place in the pH range 2 to 4 where Fe(OH) 2+ is the dominant dissolved ferric species.…”
Section: Modelling Schwertmannite Stabilitymentioning
confidence: 99%
“…Most researchers discuss Fe II photo-oxidation (Cairns-Smith 1978, and the later work of Braterman et al 1983;Borowska and Mauzerall 1986;Lundgreen et al 1989;Kim et al 2013). Short wave-length UV-C light (maximum at 267 nm; Kim et al 2013) in controlled laboratory experiments created Fe II photo-oxidation, as opposed to Fe III photo-reduction, which is induced by light over a wider range of wavelengths (200 to 450 nm, maximum at 300 nm, David and David 1976). In the absence of a protective ozone layer in the upper atmosphere, UV-C radiation could have easily penetrated Mars' thin atmosphere, as it presumably did the atmosphere of early Earth.…”
Section: Comparison Between Mineralogical Features Of Copahue-caviahumentioning
confidence: 99%
“…As early as the 1930s, the photochemical reduction of Fe(III) salts in the presence of organic substances in laboratory conditions occupied the attention of scientists (e.g., Mata Prasad and Mohile 1936;Neiger and Neuschul 1936;Gopola et al 1955;David and David 1976) and the reduction of Fe 3? to Fe 2?…”
Section: Antecedents and Previous Workmentioning
confidence: 99%
“…. The photoreduction process can take place via homogeneous (aqueous) and/or heterogeneous (solid surface) mechanisms, which are commonly represented by the following simplified equations (David and David 1976;Waite and Morel 1984;Kimball et al 1992):…”
Section: Antecedents and Previous Workmentioning
confidence: 99%
“…In previous studies, it was found that UV illumination of Fe 2+ / H 2 O 2 or Fe 3+ /H 2 O 2 system significantly increased the Fenton degradation rate of many organic substances [21], [22]. The effect of UV light is attributed to the direct • OH radical formation and regeneration of Fe 2+ from photolysis of the complex [Fe(OH)] 2+ in solution as following mechanism [23], [24]:…”
Section: Decolorization By the Uv/fenton Oxidation Processmentioning
confidence: 99%